History of Falls and The Use of Walking Aids on The Incidence of Depression in The Elderly in Indonesia - Rahmadanty, Nadiya Kamila; Novi Handayani, Maria Dara; Turana, Yuda; Hardi, Nicholas; William, William (Jurnal Kesehatan Masyarakat, 2024)
Depression is a prevalent concern, especially among the elderly who are at risk of falling and rely on walking aids. This study examines the relationship between falls, walking aid usage, and depression in the elderly using data from the Indonesian Family Life Survey 5 (IFLS-5). Conducted as a cross-sectional study, it included respondents aged ≥ 60 years. Among the 2909 respondents, the majority of respondents were aged below 75 years (13.4%), women (51.6%), and lower level of education (84.1%) with a prevalence of depression of 24,1%. The research revealed that age, education, and a history of falls were significantly associated with the occurrence of depression (p0.05). Age above 75 years old (OR: 0,653; 95% CI: 0,495-0,862) and higher education level (OR: 0,626; 95% CI: 0,483-0,811) was found to be a protective factor, while a history of falls was found to be a predictive factor to depression in elderly (OR: 1,996; 95%CI: 1,393-2,332). However, the use of walking aids showed no correlation with depression. These findings suggest that while age and education act as protective factors, a history of falls serves as a predictive factor for depression in the elderly.